Gestión de la calidad y BPM en micro y pequeños establecimientos fabricantes de bebidas alcohólicas en Colombia (2021)
The alcoholic beverage manufacturing sector in Colombia faces a challenge regarding their processess improvement, pursuant to the provisions set out in Decree 1686/2012, wherein the binding force of the certificate in good manufacturing practices was set forth, setting out an initial two years term for compliance thereof. This is how the established term has been amended several times in Decrees 1506/2014, 262/2017 and 216/2019, due to the low compliance indicators of the manufacturing sector, mainly, micro and small producing establishments. There are various difficulties detected, among which we may mention those of a technical and regulatory nature, document management, public health, income, illegality, market access, economic or financial aspects. Characterizing the compliance degree for micro and small companies producing alcoholic beverages makes it possible to identify the largest gaps and enables a technical instrument development. Thus, a guide was designed with an evaluation structure that delves into the verification of the different sanitary requirements, along with components of technical support, evaluation, and weighting based on a risk approach. Therefore, it was observed how the system management-related variables and the monitoring of actions require closer attention, based on non-compliance percentages.